From the Rhetoric of “Political Correctness” in Algerian Presidential Discourse: Elements of Discourse Analysis - Azzedine, Malek; Mokhtari , Hanya (El Omda in Linguistics and Discourse Analysis, 2022)
The discourse of the new Algerian president, Mr. Abdelmadjid Tebboune, is characterized by a rhetorical style that differs from that of his predecessors. This article aims to account for this discursive specificity by examining three expressions that frequently punctuate his speeches. Our analysis focuses in particular on segments collected from various periodic interviews granted to national and international media, as well as presidential speeches delivered during meetings involving the government and provincial governors (walis). In conclusion, we will identify the motivations behind the use of these formulaic expressions in presidential discourse.